Literacy difficulties of Dyslexic students in Bahasa Malaysia: a case study in Kelantan - Wan Norudin, Siti Wan Aminah; Baba, Suria (UMK Press, 2018)
The purpose of this qualitative case study is to explore difficulties experienced by school children with dyslexia in literacy. This study involved five school children diagnosed with dyslexia by medical practitioners. The school children were from three different primary schools and were enrolled in a dyslexia special education programme. Data were collected through multiple techniques including in-depth interviews, observations, and documentation. The findings indicated that all participants showed literacy difficulties in terms of letters reversals, inaccurate naming of letters of the alphabet, inaccurate in sounding out the spelt words, and difficulty in spelling task. Based on literacy abilities of dyslexia participants in this study, it is worth mentioning that poor readers should be explicitly taught grapheme-phoneme knowledge, syllable segmentation and phoneme manipulation. This method of teaching also was suggested by Lee and Wheldall (2010).